APPLICATION OF SEM AND QARDL MODELS IN THE PRACTICE OF ANALYSIS OF THE INFLUENCE OF EXCHANGE RATE VOLATILITY ON MACROECONOMIC INDICATORS - Roman Shchur; Andriy Pilko; Bohdan Chepyha; Mykhailo Bilyi; Sergii Stabias (Фінансово-кредитна діяльність: проблеми теорії та практики)
This study is devoted to the analysis and forecasting of the impact of the volatility of the real effective exchange rate (REER) both directly and indirectly through various channels on macroeconomic indicators in Ukraine, in particular on economic growth and public debt. The work uses the simultaneous simulative equations model (SEM) and the quantile autoregressive distributed lag model (QARDL), which made it possible to use their capabilities and form a linear and non-linear approach to assessing the impact of volatility on selected indicators in the short- and long-term. The main results demonstrate the ambiguous impact of REER volatility on economic parameters: exchange rate volatility slows down economic growth, but at the same time can reduce debt risk, mostly in the short term. The results of the quantile analysis show that individual economic indicators change the degree of their influence depending on the level of volatility and the state of the financial sector. Also, an important factor through which volatility affects economic development or changes itself is the level, dynamics and structure of trade. The proposed approach and the results obtained on its basis can serve as a methodological basis for justification and decision-making regarding the implementation of a stabilizing macroeconomic policy by state institutions.